Níveis de suplementação em pastagem de inverno sobressemeada em capim aruana para terminação de novilhos da raça Jersey - Galvan, João Carlos (2021)
The scarcity of calves is a reality in the state of Paraná, and the use of dairy males is an alternative to explore agricultural areas during the winter in crop-livestock integration systems. The objective was to evaluate the productive performance of Jersey steers with supplementation levels in winter pasture. The design was completely randomized with three treatments (8, 11 and 14 g of supplement/kg of body weight), using three replicates of area. The continuous stocking system with variable stocking rate was used, keeping the forage canopy at an average height of 19.01 cm. Two test animals were used per paddock. At the beginning of the experimental period, the animals were 13.9 months old and 236.9 kg of body weight. Pasture height, forage mass, daily accumulation rate and forage supply did not differ (P>0.05) between treatments. The animal load, animal stocking, average daily gain and body weight gain ha-1 increased (P<0.05) with the increase in the supplementation level, with a possible increase in productivity of 256 kg/ha in the variable body weight gain ha-1. Slaughter age and grazing period showed a statistical tendency of reduction with the advance of the supplementation level. Slaughter weight, hot carcass weight and carcass yield were not altered by supplementation levels. The increase in the level of supplementation from 8 to 14 g kg-1 of body weight in winter pasture increases the productive performance of Jersey steers, enabling production rates consistent with technical production systems in beef cattle.